2007
DOI: 10.2139/ssrn.979956
|View full text |Cite
|
Sign up to set email alerts
|

The Euro's Effects on Trade in a Dynamic Setting

Abstract: This paper provides an update on estimates of the euro effect on trade integration among EMU economies, taking into account the aggregate bilateral exports of 23 OECD countries for the sample period 1988-2004. We consider 13 exporting European countries and 23 importing industrialized countries We utilize the dynamic panel data estimator proposed by Blundell and Bond (1998) and introduce controls for heterogeneity. The results of our dynamic specification of the gravity equation yield an estimate of the short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
0
16
0
5
Order By: Relevance
“…The benefi ts from the use of a common currency-lower transaction costs, no exchange rate risk, better price and cost transparency-are expected to enhance openness to trade and investment, as well as to foster competition. Indeed, since the launch of the euro, bilateral trade among EA members has expanded far more rapidly than trade with other EU countries (European Commission 2008;Baldwin 2006;de Nardis, De Santis, and Vicarelli 2008). Our results suggest that these channels too have had little impact on sectoral reallocation.…”
Section: Introductionmentioning
confidence: 70%
“…The benefi ts from the use of a common currency-lower transaction costs, no exchange rate risk, better price and cost transparency-are expected to enhance openness to trade and investment, as well as to foster competition. Indeed, since the launch of the euro, bilateral trade among EA members has expanded far more rapidly than trade with other EU countries (European Commission 2008;Baldwin 2006;de Nardis, De Santis, and Vicarelli 2008). Our results suggest that these channels too have had little impact on sectoral reallocation.…”
Section: Introductionmentioning
confidence: 70%
“…The benefits from the use of a common currency -lower transaction costs, no exchange rate risk, better price and cost transparency -are expected to enhance openness to trade and investment, as well as to foster competition. Indeed, since the launch of the euro, bilateral trade among EA members has expanded far more rapidly than trade with other EU countries (European Commission 2008, Baldwin 2006, de Nardis, De Santis & Vicarelli 2008. Our results suggest that these channels too have had little impact on sectoral reallocation.…”
Section: Introductionmentioning
confidence: 73%
“…A large number of studies have attempted to estimate the effect of the EU, and in particular the formation of the eurozone, on trade patterns, with most adopting the gravity model approach (early papers include Rose, 2000, Barr et al, 2003, Flam and Nordstrom, 2006, and de Nardis et al, 2008. Rose (2009) found that trade increased by between 8 to 23 percent as a result of the eurozone, while Baldwin (2006) finds somewhat more modest results.…”
Section: Enlargement Of the Eu 1 Introductionmentioning
confidence: 99%